PEMILIHAN UMUM DENGAN MODEL â€œPARLIAMENTARY THRESHOLDâ€ MENUJU PEMERINTAHAN YANG DEMOKRATIS DI INDONESIA - Rokhim, Abdul (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2011)
Law Number 10 of 2008 as organic statute, as more comprehensive statute and comply with answering problem challenge in running general election.General election as democratic party, as symbol and also as democracy landmark. In the other side, general election as one of foremost means to reinforcing democracy living order which function as health instrument and accomplishing democracy, not as democracy aims. General election with parliamentary threshold 25% unable to realizes democratic government in Indonesia. Cause combination between presidential government system and multiparty system proved that emerging instability political, then president position become weak. Indonesia democratic parliamentary threshold in order to form legitimate governmental, by improving parliamentary threshold from 2,5 percent gradually.Keywords: general election, democracy, parliamentary threshold